1996
DOI: 10.1530/eje.0.1340093
|View full text |Cite
|
Sign up to set email alerts
|

Overnight dexamethasone suppression test: comparison of plasma and salivary cortisol measurement for the screening of Cushing's syndrome

Abstract: The overnight 1-mg dexamethasone suppression test is a very good screening test for subjects suspected of having Cushing's syndrome. To simplify the procedure, we evaluated the 1-mg dexamethasone suppression test with measurement of salivary cortisol. We performed this test with plasma and salivary cortisol measurements in 27 patients with Cushing's syndrome and 64 normal controls. The sensitivity and specificity of plasma cortisol measurements were 100% and 87%, respectively, for a cut-off point of 100 nmol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
3
33
0
2
Order By: Relevance
“…A sensitivity varying between 97% and 100% and a specificity between 77% and 100% have been variously reported, with cut-off level varying between 1.7 nmol/L and 2 nmol/L. [6][7][8][9] In the current study, we found that the sensitivity of SalF Dex was only 76.2% at the optimal cut-off of 0.85 nmol/L. Although this discrepancy with other studies might be due to a number of factors, such as the means of defining normal ranges and the criteria for diagnosing Cushing's syndrome, one important factor that is evident from our data is the method used for assaying salivary cortisol: some used electrochemiluminescence assay, 9 others used radioimmunoassay [6][7][8] ; but we measured SalF Dex with LC-MS/MS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A sensitivity varying between 97% and 100% and a specificity between 77% and 100% have been variously reported, with cut-off level varying between 1.7 nmol/L and 2 nmol/L. [6][7][8][9] In the current study, we found that the sensitivity of SalF Dex was only 76.2% at the optimal cut-off of 0.85 nmol/L. Although this discrepancy with other studies might be due to a number of factors, such as the means of defining normal ranges and the criteria for diagnosing Cushing's syndrome, one important factor that is evident from our data is the method used for assaying salivary cortisol: some used electrochemiluminescence assay, 9 others used radioimmunoassay [6][7][8] ; but we measured SalF Dex with LC-MS/MS.…”
Section: Discussionmentioning
confidence: 98%
“…5 Significant advances have been made with the use of salivary cortisol in the investigation of hypercortisolism. 3,[6][7][8][9] The availability of liquid chromatography-tandem mass spectrometry (LC-MS/MS) also enables the measurement of other glucocorticoid analytes. Among these and of particular interest is cortisone that is present in the saliva at a higher concentration-the salivary cortisone-to-cortisol ratio is up to 6-8:1…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, only a few groups investigated the validity of this method, providing cutoffs between 1.5 and 3.7 nmol/l (10,13,14,15,16). Although the Dexamethasone-suppressed salivary cortisol at 0800 h (nmol/l) Figure 1 (A) Individual peak serum cortisol levels during the insulin tolerance test and corresponding basal salivary cortisol levels at 0800 h. The two study groups are patients with adrenal insufficiency (open circles, nZ30) and patients with adrenal sufficiency (closed circles, nZ32).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma 17-hydroxyprogesterone (17OHP) and the 24-h urinary excretions of metanephrines were also assessed. Plasma cortisol was assessed by a competitive protein-binding assay (5,6). The other plasma steroids and urinary cortisol were assessed by speci庐c radioimmunoassays in routine use at the time.…”
Section: Endocrinological Studiesmentioning
confidence: 99%